Dieu a-t-il besoin du mal? - Rougé, Dominique (Romanica Silesiana)
This article aims to show how devout Christian novelists, and in particular François Mauriac, exploited the theme of evil in order to justify their religious convictions. Such evil, often identified with pleasures of the flesh, can be interpreted as self-indulgent — the protagonists are yearning for any kind of freedom and hence enable these writers (their creators) to uphold their theory. Literary works by François Mauriac, therefore, belong to the category of “committed literature,” with their author becoming God’s advocate who must be exempted from evil. Key words: God, evil, sin, flesh, salvation.